TIKHONOV'S REGULARIZATION FOR DECONVOLUTION IN THE EMPIRICAL GREEN FUNCTION METHOD AND VERTICAL DIRECTIVITY EFFECT - Kraeva N. (My University, 2004)
Application of Tikhonov's technique, using input errors for the parameter of regularization estimation, enhances the accuracy and stability of the reconstruction of a source time function (STF) by the empirical Green function (EGF) method that gives us an opportunity to use simultaneously for analysis body and surface waves data, and to estimate the horizontal and vertical directivity effects. Knowledge of the last is particularly useful for the choice of an active nodal plane of earthquakes with the dip slip fault orientation that allows us to classify these earthquakes to the interplate or intraplate types and thereby to reach the better understanding of tectonic processes in the region of interest.
Keywords: Filtration of irregular solutions; Relative source time function; Fault slip distribution; Intraplate and interplate types